Extraction of gelatin from raw chicken bones, joints and cartilages from the production of hard gelatin capsule - Rowena P. Calanog. 4 0 16; 5 (2003)
u
Thesis: (Bachelor of Science in Chemistry) - Pamantasan ng Lungsod ng Maynila, 2003.
Keywords: 2 -- 0; 6; 20; 20; 2